The Development of Pattern for Supply Chain in Digital for Manpower Management in Higher Education Institutions - Artaphon Chansamut (International Journal of Supply Chain Management, 2022)
The purpose of paper study were to study the development of pattern for supply chain in digital for manpower management in higher education institutions and evaluation of the pattern . The sample group in this study consisted of ten experts using purposive sampling. Data were analyzed by arithmetic mean and standard deviation. The research findings model seven elements namely main components, Supplier, University ( Manufacturer) , Education Customers Consumers satisfaction and Feedback. The ten experts agree that the development of pattern for supply chain in digital for manpower management in higher education institutions was high suitability.